2014
DOI: 10.1016/j.celrep.2014.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Human-Chromatin-Related Protein Interactions Identify a Demethylase Complex Required for Chromosome Segregation

Abstract: Chromatin regulation is driven by multicomponent protein complexes, which form functional modules. Deciphering the components of these modules and their interactions is central to understanding the molecular pathways these proteins are regulating, their functions, and their relation to both normal development and disease. We describe the use of affinity purifications of tagged human proteins coupled with mass spectrometry to generate a protein-protein interaction map encompassing known and predicted chromatin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 44 publications
2
78
0
Order By: Relevance
“…jmjd-5 encodes a protein of 578 aa with a C-terminal JmjC domain, present in almost all known proteins with histone demethylase activity [50]. The specificity of the catalytic activity of the mammalian homologue, JMJD5/KDM8, is controversial, with several studies reporting specific H3K36me2 demethylase activity [29, 30, 34, 51], and others reporting a possible function as a protein hydroxylase [33, 36, 52]. We therefore tested if JMJD-5 is active towards H3K36me2 by measuring the level of this mark by western blot on lysates derived from adult jmjd-5(tm3735) animals.…”
Section: Resultsmentioning
confidence: 99%
“…jmjd-5 encodes a protein of 578 aa with a C-terminal JmjC domain, present in almost all known proteins with histone demethylase activity [50]. The specificity of the catalytic activity of the mammalian homologue, JMJD5/KDM8, is controversial, with several studies reporting specific H3K36me2 demethylase activity [29, 30, 34, 51], and others reporting a possible function as a protein hydroxylase [33, 36, 52]. We therefore tested if JMJD-5 is active towards H3K36me2 by measuring the level of this mark by western blot on lysates derived from adult jmjd-5(tm3735) animals.…”
Section: Resultsmentioning
confidence: 99%
“…A caveat of heterologous expression is that, by definition, it represents overexpression; thus, it is possible that an expanded range of binding events may be observed, relative to physiological levels. In a previous study, however, we found that protein induction levels were comparable to endogenous protein levels (Marcon et al 2014). This system also facilitates motif derivation; both known and novel motifs, even in repetitive sequence, can be identified on the basis of consistency with the "recognition code," which predicts binding motifs using the specificity residues (Najafabadi et al 2015a).…”
Section: C2h2-zf Proteins Often Bind Outside Of Open Chromatinmentioning
confidence: 99%
“…Cell culture conditions, sample preparation, mass spectrometry, and derivation of spectral counts were as previously described (Marcon et al 2014). We obtained confidence scores for each putative PPI using SAINTexpress (Teo et al 2014).…”
Section: Ap-ms Proceduresmentioning
confidence: 99%
“…A role for Jmjd5 in regulating chromosomal segregation was also proposed to involve de-repression of Jmjd5 H3K36me2 demethylation activity by RCCD1 (Marcon et al, 2014). However, structural studies indicated that the JmjC domain of Jmjd5 is unlikely to accommodate a methylated lysyl residue, consistent with its limited homology to that of the JmjC KDM family (Del Rizzo et al, 2012;Wang et al, 2013).…”
Section: Kdm5mentioning
confidence: 94%